Infection Control Awareness and Self-Reported Practices among Dental Students - Ihab Ahmed Rzaij Rzaij (Universitas Muhammadiyah Sidaorjo, 2026)
Background: Infection prevention occupies a central role in dental care because of the frequent exposure to saliva, blood, and other potentially infectious materials during treatment. Objectives: The present study seeks to determine how well dental students understand established infection control procedures and to investigate the extent to which they report following these practices during their preclinical preparation and subsequent clinical training. Methods: We conducted a descriptive cross-sectional study with 51 To capture a broad range of information. The data was analyzed and interpreted using SPSS. Results: Most students appeared to understand the main infection control practices. About 88% reported washing their hands correctly, and roughly 80% used personal protective equipment appropriately. Fewer students were familiar with protocols for sharps injuries and the specific guidelines of their institution, with around six in ten demonstrating awareness. Conclusion: Control practices. However, gaps persist, especially when it comes to following institution-specific policies and reporting injuries. To overcome these gaps, it may be necessary to strengthen the infection control component of the curriculum and incorporate additional practical training opportunities in clinical settings to reinforce safe practices..